Pemanfaatan Bot Telegram sebagai Media Informasi Akademik di STMIK Hang Tuah Pekanbaru - Gilang Citra Lenardo; Herianto; Yuda Irawan (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2020)
Academic Information System is a means of supporting academic activities in STMIK HangTuah Pekanbaru by utilizing web-based technology. However, the application of webtechnology on Academic information System in STMIK Hang Tuah Pekanbaru can notalways run as desired, sometimes the information system cannot be accessed due to technicalconstraints or other factors. Based on these problems, an application was created that couldrun on instant messages and could be used via smartphones or other devices as mediainformation for students, namely utilization of telegram bot based on PHP and MySQL asacademic information at STMIK Hang Tuah Pekanbaru. This telegram bot is made using theWebhook method and can run on all operating systems that have Telegram Messengerinstalled. This bot is able to provide academic information including lecture schedules, grades,filling in krs, short semester submissions and research submissions, it is hoped that thetelegram bot will make it easier for students to get academic information through smartphonedevices that can be accessed anytime.